FINAL STATE CERTIFICATION OF GRADUATES OF THE TASHKENT MEDICAL INSTITUTE USING AN INTERACTIVE APPLICATIONS ACADEMIX 3D - Parpibaeva Dinara Ayupovna; Salayeva Muborak Saidabdullayevna; Salimova Nargiza Djurabaevna; Ergashov Nodirbek Shermuxamat o’g’li; Buvamuxamedova Nasiba Taxirovna (Journals Park Publishing, 2023)
The final state certification (FSC) of graduates of the Tashkent Medical Academy is carried out in accordance with the Law of the Republic of Uzbekistan "On Education" and "On the National Training Program" , the level of readiness of graduates to perform professional tasks and its compliance with the requirements of the State Educational Standard . The article summarizes the experience of conducting FSC of graduates of medical and pedagogical faculties using the interactive application " Academix3D" in quality one from elements appraisal funds, A Also are given results online survey, Where Graduates 2021–2022 educational of the year gave my assessment holding FSC With application virtual applications and perspectives use virtual technologies V learning.
Keywords: simulation technologies, Academix 3D, final state certification, medical education.